2018
DOI: 10.1007/s40520-018-0993-y
|View full text |Cite
|
Sign up to set email alerts
|

Fat-free mass and glucose homeostasis: is greater fat-free mass an independent predictor of insulin resistance?

Abstract: Independently of age, a greater aFFMI was an independent predictor of IR. These results suggest revisiting how we envision the link between FFM and IR and explore potential mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 41 publications
3
19
3
2
Order By: Relevance
“…In fact, IFG and IFG-IGT groups displayed higher FFM (absolute and adjusted for height) compared with NGT and IGT groups. This important result is supported by previous findings by our group and others, 19,26,27 although mechanisms that may explain this association are not well understood at this point. For example, Lebon and colleagues suggested that accumulations of intramuscular adipose tissue (particularly diacylglycerides and ceramides) and the reduced ability of muscles to oxidize lipids (which induces an alteration of the insulin signaling cascade in skeletal muscle) are negatively associated with insulin-stimulated glucose uptake.…”
Section: Discussionsupporting
confidence: 89%
“…In fact, IFG and IFG-IGT groups displayed higher FFM (absolute and adjusted for height) compared with NGT and IGT groups. This important result is supported by previous findings by our group and others, 19,26,27 although mechanisms that may explain this association are not well understood at this point. For example, Lebon and colleagues suggested that accumulations of intramuscular adipose tissue (particularly diacylglycerides and ceramides) and the reduced ability of muscles to oxidize lipids (which induces an alteration of the insulin signaling cascade in skeletal muscle) are negatively associated with insulin-stimulated glucose uptake.…”
Section: Discussionsupporting
confidence: 89%
“…Human body is composed of fat mass and fat free mass. Body composition is different by sex and age and this difference is determined by the androgens level [22]. Apart from BMI, among women with PCOS, there is a high prevalence of upper-body obesity, as shown by increased waist circumference and waist-hip ratio as compared to the BMI-matched control women [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest a “ceiling effect” at a certain level of SM, wherein adding muscle mass does not provide further metabolic advantage. In line with this, a study from Ghachem et al (2019) has identified a cut-off point of appendicular muscle mass index [7.02 muscle mass (kg)/height (m) 2 ] in sedentary older women above which IS is significantly reduced( Ghachem et al, 2019 ). Fukushima et al (2016) using a 6-month mixed-exercise and nutritional intervention in 92 middle-aged obese women found that fasting insulin and glucose decreased in those whose SM mass index (kg/m 2 ) also decreased over the course of the intervention ( Fukushima et al, 2016 ).…”
Section: Narrative Literature Reviewmentioning
confidence: 93%